Melatih Komunikasi pada Anak Usia Dini dengan Cara Bermain di Tanjung Laidong, Labuhan Batu Utara - Muhammad Walid; Randa Aditia; Nalla Shakira (Al-Balagh : Jurnal Komunikasi Islam, 2022)
It is very important to train communication in children from an early age, when children are lazy and just stay silent it results in reduced communication skills in children, the fact that communication plays an important role in child development, good communication in children comes from activities carried out by children in it through playing but very much in I regret that the world of children's play is so sporadic and even difficult to produce. Making boundaries for children's playgrounds causes them to be more interested in playing indoors by playing with cellphones or watching television sometimes it has a positive impact but it makes children not interested in playing outside such as playing hide and seek, chasing and others. other. This makes children less social with other friends, thereby reducing communication in early childhood. Therefore, communication in early childhood must be trained so that it continues to develop. One way to practice communication is to play with other children, not only that, but also to hinder the development of children.